Screening of Haliclona sp. symbiont bacteria that have the potential as MDR (Multidrug-Resistant) antibacterial from Tanjung Tiram Beach - Rasyid, Sri Anggarini; Sugireng, Sugireng; Tina, Asni Ramayana (Universitas Nahdlatul Ulama Surabaya, 2024)
Sponge Haliclona sp. is a type of sponge living in marine waters and is found in many areas of coral reef ecosystems. This study aimed to determine the potential for sponge Haliclona sp. obtained from Tanjung Tiram waters, Konawe, as a source of bioactive compounds of MDR (Multidrug-Resistant) antibacterial. The isolation method of Haliclona sp. symbiont was carried out by pouring and purification of Haliclona sp. symbiont using the scratch method. The purification results obtained 12 isolates of symbiont bacteria that were successfully isolated. Then the bacterial isolate was tested for its antibacterial ability against MRSA and ESBL Escherichia coli bacteria qualitatively using the agar diffusion method. Bacteria that have strong inhibitory activity are identified by morphological and biochemical tests. The results of the qualitative screening test produced four bacterial isolates that have inhibitory activity against MRSA (Methicilin Resistant Staphylococcus aureus) pathogenic bacteria with the isolate codes H3 and H8 belonging to the strong category while H4 and H10 belonging to the medium categoy. Additionally, two bacterial isolates that have inhibitory activity against ESBL Escherichia coli pathogenic bacteria with the isolate codes H3 and H8 belonging to the strong category. Based on morphological observations and biochemical tests, the H3 bacterial isolate was identified as the genus Corynebacterium spp. and the H8 bacterial isolate was identified as the genus Micrococcus spp. In conclusion, Haliclona sp. sponge exhibits promising potential as a source of microorganism producing antibacterial compounds, particulary againts MDR (Multidrug-Resistant) strains.